Thickness of sediments in the Congo basin based on the analysis of decompensative gravity anomalies. (July 2021) - Kaban, Mikhail K.; Delvaux, Damien; Maddaloni, Francesca; Tesauro, Magdala; Braitenberg, Carla; Petrunin, Alexey G.; El Khrepy, Sami
Abstract: The Congo basin is one of the largest intracratonic basins in the World, locating within a cold lithospheric plate. The structure of the thick sedimentary layer is investigated by seismic studies only in limited places. Here, we present a map of sedimentary thickness for the whole Congo basin, based on the inversion of the decompensative gravity anomalies. Contrary to the conventional Bouguer or isostatic gravity anomalies, the effect of the isostatic compensation of sediments is reduced in the decompensative anomalies, which provides a possibility to recover the full effect of low-density sediments. The calculated decompensative correction reaches ±70 mGal and exceeds the amplitude of the isostatic anomalies, especially in the long wavelengths. The final decompensative anomalies are negative over the whole basin and their patterns well correspond to its tectonic fragmentation. By inverting these anomalies with the predefined density-depth relationship we have obtained the sedimentary thickness map for the whole Congo basin. The maximum basement depth exceeding 10 km is found in the Lokoro basin and basins in the South. In the Lomami basin, thickness of sediments reaches about 6.5 km. It is important to note, that these deep depressions, are not covered by seismic studies. Furthermore, we found a new deep basin adjacent to the Lokonia High (on the SW side) that we propose to name as the Salonga basin. Highlights: Decompensative gravity anomalies, which reflect density variations in the upper crust, are computed for the Congo basin. A map of sedimentary thickness has been obtained for the first time for the whole Congo basin. This map demonstrates a good fit to available seismic determinations. We found several deep depressions, which were not previously covered by seismic studies. One of them is the Salonga basin.